Variable-resolution CESM2 over Antarctica (ANTSI): Monthly outputs used for evaluation. ... - Datta, Rajashree (Zenodo, 2022)
Funding generously provided by NSF Award 1952199 as well as additional support from NCAR in the creation of the dataset and the use of VRCESM. Included are outputs from an AMIP-style (data-driven ocean and sea ice) simulation of Variable-Resolution CESM2 from 1979-2015. Resolution is 1° globally with a refined 0.25° resolution over the Southern Ocean as well over the Antarctic ice sheet. Outputs are at a monthly timescale, and include those variables relevant for evaluation. Each netcdf file ends with several relevant tags to indicate <source>.<output deisgnator>.<variable>.<time period>.nc. Atmospheric variables are labeled with "cam" whereas ice sheet variables are labeled with "clm2". clm2.h0.SNOW.198901-199812.nc cam.h1.Q.198901-199812.nc Variables are described for CESM2 (see NCAR documentation for clm and cam) Variables included for cam include FLDS, FLNS, CLDICE, CLDLIQ, LHFLX, PRECC, PRECL, PRECSC, PS,Q, SHFLX, U, V, Z3 Variables included for clm2 include FIRA, FIRE, FLDS, ...